(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: No definitive treatment is available for Lupus. Moringaoleiferais one of promisingnovel treatments in Lupus trough anti inflammation and immunosupresion. Mean platelet volume andneutrophil to lymphocyte ratio used to measure degree of lupus activities. Objective: Our study wasaimed to identify the effect of Moringaoleiferaextract on the Mean platelet volume and neutrophil to lymphocyte ratio in lupus. Methods: This experimental study was conducted in 30 lupus patients,located in the rheumatology clinic at Moewardi General Hospital in January-March 2019. The studygroup was divided into two groups: the treatment research group received 2 grams of moringa extractper day and the placebo group. The study was conducted for 4 weeks and was evaluated when thestudy was completed. MPV and NLR examination using a hemocytometer. Statistical analysis wasperformed using paired T test, independent T-test. The p value was considered significant when the p < 0.05. Results: The results showed a decrease in MPV (delta MPV = 4.141; r 0.656; p-0.02) anda decrease in Neurophil to lymfocyte ratio (delta NLR = 4.1391; r 0.489; p-0.04) Conclusion: Thestudy demonstrated the effect of Moringaoleiferaleaf extract on reduced Mean platelet volume andneutrophil to lymphocyte ratio in lupus Bangladesh Journal of Medical Science Vol.20(1) 2021 p.68-73